The Age of Climate Change: Cultural Change Temporalities and Crisis Awareness - Kverndokk, Kyrre (Journal of Northern Studies, 2021)
This article elaborates the multiple temporalities of climate change discourses and practises and discusses some possible common denominators in the timescales and time structures related to global warming. It first examines some of the key concepts in climate research, before discussing vernacular notions of time. Finally, some expressions and tropes that have impacted a trans-national popular climate discourse are examined. The timescales and temporal structures discussed have quite different extents, from millions of years to a generation or two. Some of these temporalities are chronological while others are cyclical. They are also about completely different phenomena—from geology to society and kin. However, the article concludes that they are interconnected through their focus on the present moment, and the temporal structure of kairos, in Frank Kermode’s understanding of the term. In that regard, they are temporalities expressing a notion of a contemporary crisis, that is both urgent and of almost cosmological propositions.